2008
DOI: 10.1002/iub.91
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ions in neuronal degeneration

Abstract: Neuronal Ca2+ homeostasis and Ca2+ signaling regulate multiple neuronal functions, including synaptic transmission, plasticity, and cell survival. Therefore disturbances in Ca2+ homeostasis can affect the well‐being of the neuron in different ways and to various degrees. Ca2+ homeostasis undergoes subtle dysregulation in the physiological ageing. Products of energy metabolism accumulating with age together with oxidative stress gradually impair Ca2+ homeostasis, making neurons more vulnerable to additional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
208
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(214 citation statements)
references
References 181 publications
4
208
0
2
Order By: Relevance
“…C ells must tightly regulate Ca 2+ homeostasis to avoid pathological perturbations and cell death (1). For example, a profound disruption of Ca 2+ homeostasis is seen in Parkinson disease (PD), the second most common neurodegenerative disorder.…”
mentioning
confidence: 99%
“…C ells must tightly regulate Ca 2+ homeostasis to avoid pathological perturbations and cell death (1). For example, a profound disruption of Ca 2+ homeostasis is seen in Parkinson disease (PD), the second most common neurodegenerative disorder.…”
mentioning
confidence: 99%
“…It has been showed that ROS mediated dysregulation of intracellular calcium signaling pathways affected the cell severely. Altered calcium homeostasis could further initiate the excitotoxic effects which lead to activation of glutamate receptors and neuronal apoptosis under diseased condition [59][60][61][62] .…”
Section: (B)mentioning
confidence: 99%
“…NMDA receptors permit calcium to enter the cell when combining with glutamate, which is imperative for cell signaling, and then for learning and memory [112]. However, excess glutamate can be released from impaired neurons in AD, resulting in chronic overexposure to calcium, which can in turn accelerate neuron impairment [113]. Memantine can partially block the NMDA receptors, and then prevent this destructive chain of events [108,109].…”
Section: Symptomatic Therapies: Approved Drugs For Treatment In Alzhementioning
confidence: 99%